Animals in Spring - Fretland VanVoorst, Jenny 1972- (Minneapolis, MN : Bullfrog Books, 2016)
"This photo-illustrated book for beginning readers describes the behavior of animals in the spring as they give birth, raise their young, and adapt to the changing season. Includes picture glossary and index."--
Life is good -- Baby animals of spring.
Includes index.
Ages 5-8
K to grade 3
Accelerated Reader AR
Keywords: Animal behavior -- Juvenile literature; Animals -- Juvenile literature; Spring -- Juvenile literature